Meta-analytical model of the relationship between learning motivation, self-efficacy, and academic achievement in online learning - Hermawan Setiawan; Widodo Widodo; Merry Lapasau; Sunar Abdul Wahid; Acep Musliman (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
The transformation of global education towards e-learning poses challenges to students' motivation and self-efficacy, impacting inequalities in academic achievement. A number of studies indicate that the relationship between motivation, self-confidence, and achievement remains complex and warrants further investigation. This study conducted a meta-analysis to assess the strength of the relationship between motivation, self-efficacy, and academic achievement in the context of digital learning. By analyzing 52 recent studies (2004–2025), we used a randomized effects model to account for heterogeneity between studies. The correlation coefficient reported in each study was converted to Fisher's Z to normalize the distribution of effects. Subsequently, the meta-analytic SEM was performed to test the self-efficacy mediation model. The results of the meta-analysis showed that the combined correlation between motivation and self-efficacy (r = 0.52) and motivation and academic achievement (r = 0.44) exhibited a moderate to strong ffect. The meta- structural equation modelling (SEM) analysis confirmed that self-efficacy mediates a partial influence of motivation on Academic Achievement (β indirect = 0.355, 36% of the total influence). Theoretically, these results strengthen social cognitive theory (Bandura) and self-determination theory (Deci & Ryan) in the field of e-learning. Practically, the results suggest that teachers and institutions should develop interventions that increase students' intrinsic motivation and self-confidence (e.g., through autonomy-supporting learning) and support educational policies that incorporate non-cognitive psychological indicators into the curriculum. This study provides a more accurate estimate of average effects and supports the development of the theory and practice of digital education based on cross-cultural evidence.